Evaluation of User Satisfaction with the Tourism and Culture Office Website of Ciamis Regency - Dedeng Yusuf Maolani; Siti Alia (UIN Sunan Gunung Djati Bandung, 2024)
One of the implementations of E-Government by the local government is the creation of the Dispar Ciamis Regency website, developed by the Ciamis Regency Government. This initiative aligns with Ciamis Regency Regional Regulation No. 19 of 2011, Article 27, which mandates the local government to provide various tourism information, legal protection, safety, comfort, and security for tourists. Therefore, the government is obliged to provide tourism-related information on the official website while considering user security, legal protection, comfort, and safety. This study utilizes the E-GovQual method to assess user satisfaction with the services provided by the Dispar Ciamis Regency website. A total of 54 responses were collected. The analysis methods employed include Scriptural Hash Table Analysis, Validity and Reliability Analysis, and Hypothesis Analysis. The study results indicate that the variables of usability, trust, interactive environment functionality, reliability, content, and information display, as well as citizen support, do not influence users' intention to use (REI), except for the content, information display, and citizen support variables, which influence user satisfaction (AS) or intention. Additionally, to enhance user trust in the Dispar Ciamis Regency website, it is necessary to include features that measure the level of understanding between the website administrators and users regarding each applicable rule or policy.